Inovasi Pemanasan dengan Lompat Tali: Analisis Komparatif Kecepatan Siswa Sekolah Bilingual di Tiongkok - Eghie Marvianissa; Mochamad Ridwan; Muchamad Arif Al Ardha (Indonesian Journal of Physical Education and Sport Science, 2025)
Study purpose. This study aimed to explore the innovative use of skipping warm-ups to improve students' running speed in a bilingual school in China. Materials and Methods. Using a quasi-experimental approach and a pretest-posttest design, this study involved 21 ninth-grade students, consisting of 13 girls and 8 boys. The warm-up consisted of various skipping exercises for 5 minutes, followed by a 100-meter run test. Results. The results showed a decrease in average running time after the warm-up, but this difference was not statistically significant (p = 0.085). This finding suggests that while skipping exercises can improve overall physical fitness, fatigue experienced by students during the warm-up may mitigate its impact on running speed. Factors such as the short warm-up duration, high intensity, and differences in students' fitness levels were the main reasons why the results did not reach the expected significance. Furthermore, Shanghai's summer weather, high temperatures and humidity, can exacerbate fatigue levels during the warm-up, which in turn can reduce the effectiveness of physical exercise. Conclusion. This study suggests the need to adjust the duration and intensity of training to optimize the results of warm-up exercises with skipping, as well as the importance of considering students' motivational factors in significantly increasing speed.